2009
DOI: 10.1176/appi.neuropsych.21.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Insular Function Predicts Positional Blood Pressure in Nondemented Elderly

Abstract: 40% of non-demented octogenarians have Braak stages consistent with insular involvement, and may be at risk for “age–related” autonomic dysfunction. We examined the association between insular resting Cerebral Blood Flow (rCBF) and cardiovascular functions in 29 non-demented elderly subjects who were highly screened to exclude comorbid cardiovascular disease. Mean insular rCBF was significantly higher on the right (R) than left (L). However, 35.4% of subjects had L dominant rCBF = a "HIGH” risk group. R insula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The observations have been consistent with those observed using SPECT. Using dynamic contrast method, CBF has been found significantly reduced in insular cortex [ 83 , 84 ]. Because the insula is an important brain structure for the autonomic control of blood pressure and heart rate, the observations suggested that AD pathology has effect on ventral autonomic cardioregulatory dysfunction.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The observations have been consistent with those observed using SPECT. Using dynamic contrast method, CBF has been found significantly reduced in insular cortex [ 83 , 84 ]. Because the insula is an important brain structure for the autonomic control of blood pressure and heart rate, the observations suggested that AD pathology has effect on ventral autonomic cardioregulatory dysfunction.…”
Section: Alzheimer's Diseasementioning
confidence: 99%